2015
DOI: 10.1080/03630242.2015.1088116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music listening on stress, anxiety, and sleep quality for sleep-disturbed pregnant women

Abstract: Prenatal sleep disturbance has been associated with undesirable birthing outcomes. To determine the effectiveness of listening to music at home in improving sleep quality, 121 Taiwanese pregnant women with poor sleep quality (Pittsburgh Sleep Quality Index [PSQI] score > 5) were systematically assigned, with a random start to music listening (n = 61) or control (n = 60) group. Participants in the music listening group self-regulated listening to music in addition to receiving general prenatal care similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 37 publications
7
93
0
8
Order By: Relevance
“…Quando aplicados questionários, foi descoberto uma redução nos níveis de ansiedade e depressão e uma melhora da qualidade do sono das gestantes (LIU et al, 2015). …”
Section: Musicoterapia No Pré-natalunclassified
“…Quando aplicados questionários, foi descoberto uma redução nos níveis de ansiedade e depressão e uma melhora da qualidade do sono das gestantes (LIU et al, 2015). …”
Section: Musicoterapia No Pré-natalunclassified
“…The type of music that can help relaxation and control anxiety is a type of relaxing music with a tempo of 60 beats/minute. [7,8] Music that played can make someone calm. The mind is allowed to flow to the beat, remembering happy things, dreaming of a dream, or even describing the problem [7] .Music enters through the ear and stimulates the hypothalamus to produce dopamine and reduces the hormone cortisol.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Music that played can make someone calm. The mind is allowed to flow to the beat, remembering happy things, dreaming of a dream, or even describing the problem [7] .Music enters through the ear and stimulates the hypothalamus to produce dopamine and reduces the hormone cortisol. So that the mother feels calm and happy, this condition, if maintained, will improve physical, psychological, social and spiritual health [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Another approach utilized music developed from EEG patterns and similarly found substantial improvements in sleep patterns in patients with insomnia [19]. Individual studies as well as systematic reviews and meta-analyses have shown that listening to music has also been shown to be helpful in promoting sleep [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%